Social parasitism and the molecular basis of phenotypic evolution - Cini, Alessandro; Patalano, Solenn; Segonds-Pichon, Anne; Busby, George B. J.; Cervo, Rita; Sumner, Seirian (Frontiers in Genetics, 2015)
Contrasting phenotypes arise from similar genomes through a combination of losses, gains, co-option and modifications of inherited genomic material. Understanding the molecular basis of this phenotypic diversity is a fundamental challenge in modern evolutionary biology. Comparisons of the genes and their expression patterns underlying traits in pairs of closely related species offer an unrivalled opportunity to evaluate the extent to which genomic material is reorganised to produce novel traits. Advances in molecular methods now allow us to dissect the molecular machinery underlying phenotypic diversity in almost any organism, from single-celled organisms to the most complex vertebrates. Here we discuss how comparisons of social parasites and their free-living hosts may provide unique insights into the molecular basis of phenotypic evolution. Social parasites evolve from a social ancestor and are specialised to exploit the socially acquired resources of their closely-related, free-living social host. Molecular comparisons of such species pairs can reveal how genomic material is re-organised in the loss of ancestral traits (i.e. of free-living traits in the parasites) and the gain of new ones (i.e. specialist traits required for a parasitic lifestyle). We define hypotheses on the molecular basis of phenotypes in the evolution of social parasitism and discuss their wider application in understanding the molecular basis of phenotypic diversity within the theoretical framework of phenotypic plasticity and shifting reaction norms. Currently there are no data available to test these hypotheses, and so we also provide some proof of concept data for our conceptual model using the paper wasp social parasite-host system (Polistes sulcifer - Polistes dominula). This conceptual framework and first empirical data provide a spring-board for directing future genomic analyses on exploiting social parasites as a route to understanding the evolution of phenotypic specialisation.